A Survey of Available Literature on Rural Women and Women’s Work in Agriculture - Sharma, Arti (International Journal of Social Sciences and Management, 2014)
Literature review is an essential part for research. Before starting research on a meticulous topic, one needs to map the types of available writings on the topic of research. Literature review helps in choosing a topic for research which has not been studied yet or less studied. It also tells the importance of research topic. This study assembles all the major categories of research on rural women and their work in agriculture. DOI: http://dx.doi.org/10.3126/ijssm.v1i2.10284 Int. J. Soc. Sci. Manage. Vol-1, issue-2: 69-73